Graphene dispersion, graphene resin powder, and battery
By formulating a graphene dispersion with controlled viscosity and polymer weight average molecular weight, the aggregation and re-agglomeration issues are addressed, resulting in highly conductive graphene resin films and batteries with enhanced discharge capacity.
Patent Information
- Application Number
- JP2022545726
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-08-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-08-27
AI Technical Summary
Graphene tends to aggregate due to van der Waals forces, making it difficult to disperse well in a dispersion medium, and when the dispersion is dried to form a film, re-agglomeration occurs, reducing dispersibility. Additionally, high polymer content can increase surface resistance and polyvinylpyrrolidone can hinder film formation.
A graphene dispersion liquid is formulated with a polymer of specific weight average molecular weight, adjusted to achieve viscosity within certain ranges measured at different rotational speeds, ensuring good dispersibility and conductivity by balancing viscosity ratios.
The solution results in a graphene dispersion with improved dispersibility and conductivity, allowing for the formation of highly conductive graphene resin films and batteries with high discharge capacity retention.
Smart Images

Figure 0007601885000001 
Figure 0007601885000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a graphene dispersion, a graphene resin powder, and a battery, and in particular to a graphene dispersion, a graphene resin powder obtained by drying the graphene dispersion, and a battery obtained using the graphene resin powder. [Background technology]
[0002] Graphene, a substance containing two-dimensional crystals of carbon atoms, is a material that has attracted much attention. Graphene has excellent electrical, thermal, optical, and mechanical properties. Graphene is expected to be used in a wide range of applications, for example, in graphene-based composite materials, nanoelectronics, flexible / transparent electronics, nanocomposite materials, supercapacitors, batteries, hydrogen storage, nanomedicine, and bioengineering materials. In particular, films with graphene dispersed therein are expected to be used as electromagnetic wave shielding materials, electromagnetic wave absorbing materials, electrode materials for fuel cells, heat dissipation materials, and the like.
[0003] In order to form a film in which graphene is dispersed, the graphene needs to be dispersed in a dispersion medium. Here, as a dispersion medium in which graphene is dispersed, a dispersion in which a thermoplastic resin and a carbon material having a graphene structure are dissolved or dispersed in a halogenated aromatic solvent is known (see Patent Document 1). As a dispersion medium in which graphene is dispersed, a dispersion in which graphene is stably dispersed in a solvent by polymethylpyrrolidone is known (see Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-224810 A [Patent Document 2] JP 2014-009104 A Summary of the Invention
[0005] The present disclosure relates to the following: [1] A graphene dispersion in which graphene and a polymer are dispersed or dissolved in a solvent, the polymer having a weight-average molecular weight of 10,000 to 800,000; the graphene dispersion has a viscosity of 500 to 10,000 (mPa s) measured using a Brookfield viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm; and a value obtained by dividing the viscosity of the graphene dispersion measured using a Brookfield viscometer at a measurement temperature of 25° C. and a rotation speed of 5 rpm by the viscosity of the graphene dispersion measured using a Brookfield viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm is 1.2 to 5.0. [2] A graphene resin powder obtained by drying the graphene dispersion liquid described in [1] above. [3] A battery using the graphene resin powder described in [2] above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] Since graphene has a tendency to aggregate due to van der Waals forces, it is difficult to disperse graphene well in a dispersion medium. In addition, when the solvent is dried to produce a film from a graphene dispersion, the graphene may re-aggregate, resulting in a decrease in dispersibility. In addition, if the dispersion contains a large amount of polymer, the polymer component may be present on the surface of the film when it is made into a film, increasing the surface resistance and decreasing the conductivity. Furthermore, if the dispersion contains polyvinylpyrrolidone, it may not be possible to form a film.
[0007] The present inventors dispersed graphene and a polymer having a predetermined weight average molecular weight in a solvent, and adjusted the value measured using a Brookfield viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm (hereinafter, the viscosity measurement is the value measured using a Brookfield viscometer) to be within a predetermined range. Furthermore, the present inventors adjusted the value obtained by dividing the viscosity measured at a measurement temperature of 25° C. and a rotation speed of 5 rpm by the viscosity measured at a measurement temperature of 25° C. and a rotation speed of 50 rpm to be within a predetermined range. As a result, they found that a graphene dispersion having good dispersibility and capable of forming a graphene resin film having high conductivity can be obtained. Furthermore, when the graphene resin powder obtained by drying the obtained graphene dispersion was dissolved again in a solvent, a graphene dispersion having good dispersibility was obtained. The present inventors found that when a film was formed using the graphene dispersion, the film-forming property (dispersibility) was good. Furthermore, the present inventors have found that when graphene resin powder is used as a negative electrode material for a secondary battery, the battery has a high high-rate discharge capacity retention rate.
[0008] Hereinafter, the present disclosure will be described in detail with reference to one embodiment. In this specification, the expression "XX to YY" means "XX or more and YY or less." In addition, in this specification, the lower limit value and the upper limit value described in stages for a numerical range (for example, a range of content, etc.) can be independently combined. In addition, in the numerical range described in this specification, the upper limit value or the lower limit value of the numerical range may be replaced with a value shown in the examples. In this specification, "graphene" means "a sheet-like material containing 10 or fewer layers of sp2-bonded carbon atoms." In this specification, "modified graphite" means "a sheet-like substance (excluding graphene) having a size (long side) of 0.1 nm to 50 μm and containing more than 10 layers and not more than 2000 layers of sp2 bonded carbon atoms." The size of the "modified graphite" was measured using a scanning electron microscope (Hitachi High-Tech Corporation, Model S-3400NX). The thickness of the "modified graphite" was measured using an X-ray diffractometer (PANalytical Corporation, Model X'Pert PRO), and the number of layers was calculated from the layer spacing of the (002) diffraction line and the crystal thickness. In this specification, "graphene resin powder" means "graphene and modified graphite coated with resin."
[0009] (Graphene dispersion) The graphene dispersion of the present embodiment contains graphene, a polymer, and a solvent, and may further contain modified graphite and other components as necessary. The dispersibility of the graphene dispersion can be measured by absorbance using a spectrophotometer, as described in the examples.
[0010] The viscosity of the graphene dispersion is not particularly limited as long as it is 500 to 10,000 mPa·s when measured at a measurement temperature of 25° C. and a rotation speed of 50 rpm, and may be 700 to 8,000 mPa·s. If the viscosity of the graphene dispersion is 500 mPa s or more when measured at a measurement temperature of 25°C and a rotation speed of 50 rpm, structural viscosity is likely to be expressed and graphene is less likely to aggregate. On the other hand, if the viscosity of the graphene dispersion is 10,000 mPa s or less when measured at a measurement temperature of 25°C and a rotation speed of 50 rpm, workability such as coatability can be improved.
[0011] The viscosity of the graphene dispersion is not particularly limited and may be 600 to 50,000 mPa·s or 840 to 40,000 mPa·s when measured at a measurement temperature of 25°C and a rotation speed of 5 rpm. If the viscosity of the graphene dispersion is 600 mPa·s or more when measured at a measurement temperature of 25°C and a rotation speed of 5 rpm, it is greater than the surface tension of the solvent, and a uniform coating film can be obtained. On the other hand, if the viscosity of the graphene dispersion is 50,000 mPa·s or less when measured at a measurement temperature of 25°C and a rotation speed of 5 rpm, workability such as coatability can be improved, and a continuous coating film without uncoated areas can be obtained.
[0012] The value obtained by dividing the viscosity of the graphene dispersion measured at a rotation speed of 5 rpm by the viscosity of the graphene dispersion measured at a rotation speed of 50 rpm (hereinafter, sometimes referred to as "viscosity ratio") is not particularly limited as long as it is 1.2 to 5.0, and may be 2.0 to 4.0. By setting the above viscosity ratio to the above lower limit value or more, the graphene dispersion exhibits structural viscosity. This is because the secondary bond between the polymers exerts a repulsive force that is nearly 10 times greater than the van der Waals force between the graphenes. Therefore, even if the graphene is highly concentrated, it is possible to stably disperse the graphene and modified graphite, and to reduce aggregation of the graphene and modified graphite. In addition, by setting the above viscosity ratio to the above upper limit value or less, the graphene dispersion has appropriate fluidity. Therefore, it is suitable for coating properties when forming a film, and a continuous homogeneous film can be formed. In addition, examples of methods for adjusting the viscosity ratio within the above range (obtaining the optimal structural viscosity) include using a polymer that is a predetermined anionic polymer, using a predetermined amount (relatively small amount) of a polymer with a large weight average molecular weight, and using a polymer with a degree of etherification of 0.5 to 2.2. In this specification, the "degree of etherification" is a value measured by the nitric acid methanol method.
[0013] <Graphene> The graphene is not particularly limited as long as it can be turned into graphene in the graphene dispersion. For example, the graphene may be obtained from modified graphite. The method for producing graphene from modified graphite is not particularly limited. For example, mechanical exfoliation, CVD, oxidation-reduction, chemical exfoliation, etc. may be used alone or in combination of two or more. The carbon atom content in graphene is not particularly limited, and may be 95 mass % or more, 99 mass % or more, or 100 mass %. The content of impurities in graphene is not particularly limited, and may be 5 mass % or less, 1 mass % or less, or 0 mass %. The size of graphene is not particularly limited and may be 0.1 nm to 50 μm, 0.5 nm to 10 μm, or 0.1 μm to 2 μm. The size of graphene refers to the longer of the length and width (long side) of graphene. When the size of graphene is 0.1 nm or more, the thermal conductivity of graphene is improved, whereas when the size of graphene is 50 μm or less, the dispersibility of graphene is improved.
[0014] The content of graphene in the graphene dispersion is not particularly limited, and may be 0.1 mass % to 25 mass %, 1.0 mass % to 15 mass %, or 3.0 mass % to 10 mass % with respect to the solvent in the graphene dispersion.
[0015] <<Modified graphite>> The modified graphite can be produced, for example, from natural graphite. The modified graphite may contain no atoms other than carbon atoms, or may contain atoms other than carbon atoms, for example, 10% by mass or less of oxygen atoms. When the content of oxygen atoms is 10% by mass or less, the thermal conductivity of the resulting graphene is improved. The carbon atom content in the modified graphite is not particularly limited, and may be 70% by mass to 100% by mass, 80% by mass to 98% by mass, or 85% by mass to 95% by mass. The size of the modified graphite is not particularly limited as long as it is 0.1 nm to 50 μm, and may be 0.5 nm to 20 μm. The size of the modified graphite refers to the longer of the length and width (long side) of the modified graphite. When the size of the modified graphite is 0.1 nm or more, the thermal conductivity of the modified graphite is improved, whereas when the size of the modified graphite is 50 μm or less, the dispersibility of the modified graphite is improved.
[0016] The number of layers of the modified graphite is not particularly limited as long as it is more than 10 layers and not more than 2000 layers. From the viewpoint of improving flexibility and dispersibility, it may be more than 10 layers and not more than 200 layers, or may be more than 10 layers and not more than 30 layers.
[0017] <Polymer> The polymer has a weight-average molecular weight of 10,000 to 800,000 and is dissolved or dispersed in a solvent. Furthermore, there is no particular limitation as long as the polymer has a high viscosity at a low shear rate in the dispersion and exhibits a property of causing a decrease in viscosity at a high shear rate (property of structural viscosity). The polymer may be either a water-soluble polymer or a water-insoluble polymer, or may be an anionic polymer. Furthermore, when the polymer has a strong affinity for graphene, it is easy to coat the graphene. Therefore, the graphene and modified graphite are less likely to aggregate or precipitate, and can be stored for a long period of time. In this specification, the "weight average molecular weight of a polymer" can be measured by gel permeation chromatography (using a GPC apparatus (HLC-8120GPC) manufactured by Tosoh Corporation, two columns (TSK-GEL, α-M), at a flow rate of 1 mL / min) using polystyrene with a known molecular weight as a standard substance.
[0018] <<Aqueous polymer>> The aqueous polymer is not particularly limited, and examples thereof include xanthan gum, welan gum, succinoglycan, guar gum, locust bean gum, tamarind gum, pectin and derivatives thereof, thickening polysaccharides having gelling ability, such as carboxymethylcellulose (CMC) salts, hydroxyethyl cellulose, alginates, glucomannan, agar, and lambda (λ) carrageenan; synthetic resins such as polyvinyl alcohol having a weight-average molecular weight of 100,000 to 150,000, polymers having a weight-average molecular weight of 100,000 to 150,000 mainly composed of alkyl methacrylate esters, and crosslinked acrylic acid polymers; and nonionic thickeners (surfactants) of PEG type with an HLB of 8 to 12.
[0019] <<Anionic polymer>> The functional group possessed by the anionic polymer is not particularly limited, and examples thereof include a carbonyl group, a hydroxyl group, a sulfonic acid group, and a phosphate group. The anionic polymer is not particularly limited, and may be, for example, a natural or semi-synthetic polymeric carboxylic acid from the viewpoint of easily exhibiting structural viscosity by hydrogen bonding between hydroxyl groups, and examples thereof include salts having carboxyl groups such as alginic acid, carboxymethylcellulose, hydroxycarboxymethylcellulose, carboxymethylated starch, gum arabic, gum tragacanth, and pectin hyaluronic acid.
[0020] The content of the polymer in the graphene dispersion is not particularly limited, and may be 1 to 100 mg / g, or 5 to 50 mg / g, relative to the solvent in the graphene dispersion. When the content of the polymer in the graphene dispersion is 1 mg / g or more, structural viscosity is expressed, and graphene becomes less likely to aggregate. On the other hand, when the content of the polymer in the graphene dispersion is 100 mg / g or less, the surface resistance when a film is formed is reduced, and the coatability (workability) of the graphene dispersion is improved.
[0021] The weight-average molecular weight of the polymer is not particularly limited as long as it is 10,000 to 800,000, and may be 50,000 to 600,000 or 100,000 to 500,000. When the weight-average molecular weight of the polymer is 10,000 or more, the viscosity ratio of the graphene dispersion can be adjusted to 1.2 or more, and the graphene dispersion exhibits structural viscosity, making it difficult for graphene to aggregate. On the other hand, when the weight-average molecular weight of the polymer is 800,000 or less, workability such as coating property is improved. The degree of etherification of the polymer is not particularly limited and may be 0.5 to 2.2, or 0.7 to 1.5. When the degree of etherification of the polymer is 0.5 to 2.2, structural viscosity is easily developed.
[0022] Generally, polymers are used as thickeners to disperse nanofillers. In this case, the amount of polymer (thickener) is usually at least 200 mg / g of the solvent. The polymer (thickener) is adsorbed to solids such as fillers, and the concentration of the polymer (thickener) in the solvent decreases. Therefore, a large amount of polymer (thickener) is required to obtain the structural viscosity required for nanofillers to disperse. However, if the amount of polymer (thickener) is too large, when it is made into a film, the polymer (thickener) increases the surface resistance, resulting in poor conductivity. In the graphene dispersion of the present embodiment, since graphene is the dispersoid, the amount of polymer (thickener) adsorbed to the solid matter is small due to its shape. Even a small amount of polymer (thickener) of less than 200 mg / g can improve dispersibility and reduce surface resistance.
[0023] <Solvent> The solvent is not particularly limited as long as it can disperse graphene and dissolve or disperse a polymer, and may be a polar solvent. The polar solvent is not particularly limited, and examples thereof include water, methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol (IPA)), butanol, acetone, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone. These may be used alone or in combination of two or more. Among these, water, methanol, ethanol, 1-propanol, 2-propanol, N-methylpyrrolidone, N,N-dimethylformamide, and a mixed solvent of at least two of these may be selected in terms of high affinity with graphene. A mixed solvent containing water and alcohol may be selected, and water / 2-propanol with a mixing ratio (volume ratio) of 50 / 50 to 70 / 30 may be selected. When a non-polar solvent is used as the solvent, graphene is difficult to disperse in the solvent.
[0024] <Other ingredients> The graphene dispersion of the present embodiment may contain other components, which are not particularly limited and may include nanofillers, fillers such as expanded graphite and flake graphite (excluding nanofillers), and additives such as thickeners, viscosity adjusters, resins, curing agents, flame retardants, foaming agents, and ultraviolet absorbers. The total amount of graphene, modified graphite, and polymers having a weight-average molecular weight of 10,000 to 800,000 in the solid content (i.e., components excluding the solvent) of the graphene dispersion of this embodiment may be 60 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 100 mass%.
[0025] <Method for preparing graphene dispersion> The method for producing the graphene dispersion of the present embodiment is not particularly limited, and a known method for producing a graphene dispersion can be used. For example, modified graphite is put into a solvent, and liquid phase exfoliation is performed by ultrasonic dispersion or the like, and the graphene is exfoliated, and then a polymer is added, and the mixture is mixed under vacuum using mechanical stirring or the like to obtain a graphene dispersion. The amount of modified graphite added to the solvent may be 5 to 100 mg / g, or may be 10 to 70 mg / g. If the amount of modified graphite added to the solvent is too small, the graphene concentration in the obtained graphene dispersion will be low. On the other hand, if the amount of modified graphite added to the solvent is too large, the modified graphite is difficult to exfoliate and difficult to become graphene.
[0026] <Graphene resin film> A graphene resin film is formed using the graphene dispersion of the present embodiment.
[0027] <<How to manufacture graphene resin film from graphene dispersion>> In the graphene dispersion of the present embodiment, graphene is present almost uniformly in the solvent, and modified graphite may be present almost uniformly. As a result, a film formed using the graphene dispersion has good film-forming properties and contains graphene almost uniformly. There is no particular limitation on the method for producing a film formed using the graphene dispersion of the present embodiment, and examples of the method include a method of applying the graphene dispersion onto a desired surface of a substrate and solidifying the graphene dispersion to form a film.
[0028] The material of the substrate for forming a film formed using the graphene dispersion of the present embodiment is not particularly limited as long as a desired film is formed, and examples thereof include ceramics such as glass, silica, alumina, titanium oxide, silicon carbide, silicon nitride, and aluminum nitride; metals such as silicon, aluminum, iron, and nickel; and thermoplastic resins such as acrylic resin, polyester, polycarbonate, polyamide, polyimide, polyphenylene sulfide, polyether ether ketone, polyphenylene ether, polyether nitrile, polyamide imide, polyether sulfone, polysulfone, and polyether imide.
[0029] The substrate for forming a film using the graphene dispersion of the present embodiment is not particularly limited as long as a film can be formed using the graphene dispersion, and examples thereof include membranous bodies such as films and sheets (including woven or nonwoven fabrics formed from fibers); molded bodies other than membranous bodies; powders and granular bodies; and the like.
[0030] In order to improve adhesion to a film formed using the graphene dispersion of this embodiment, the surface of the substrate may be subjected to a corona discharge treatment or a plasma discharge treatment.
[0031] As a coating method for forming a film using the graphene dispersion of the present embodiment, various general coating methods can be adopted depending on the viscosity of the graphene dispersion and the desired shape and size of the film. The coating method is not particularly limited, and examples thereof include a dripping / dipping method, a doctor blade coating method, a knife coating method, a bar coating method, a spin coating method, a gravure coating method, a screen coating method, and a spraying method using a spray.
[0032] After the graphene dispersion is applied to the substrate, the substrate to which the graphene dispersion is applied may be heat-treated in order to remove the dispersion medium in the graphene dispersion. The heat treatment temperature varies depending on the volatility of the solvent, the type of substrate, the heating atmosphere, and the function to be imparted by the film formability. The heat treatment temperature is 50 to 300° C. when the substrate is a ceramic or metal, and 20 to 250° C. when the substrate is a thermoplastic resin. These temperatures are not particularly limited as long as they do not cause deterioration of the graphene or the substrate.
[0033] The film formed by using the graphene dispersion of the present embodiment may be fixed on a substrate or may be peeled off from the substrate. The film fixed on the substrate can impart functions such as electrical conductivity, thermal conductivity, and electromagnetic wave absorption to the substrate.
[0034] The thickness of the film formed by using the graphene dispersion of the present embodiment is not particularly limited, and may be 50 μm or less, or may be 30 μm or less. If the film thickness is 50 μm or less, deterioration of leveling properties, etc. is unlikely to occur. The lower limit of the film thickness is not particularly limited as long as it is within a range in which a uniform film can be obtained.
[0035] <Molded products other than films formed using graphene dispersions> The graphene dispersion of the present embodiment can be used as a material for a molded product obtained by mixing the graphene dispersion with other organic polymer materials, etc., in addition to a film. For example, the graphene dispersion can be used as a material for a molded product having electrical conductivity, thermal conductivity, electromagnetic wave absorption properties, etc., particularly a molded product such as an electrode that requires electrical conductivity.
[0036] (Graphene resin powder) The graphene resin powder of the present embodiment is obtained by drying the graphene dispersion of the present embodiment.
[0037] The graphene resin powder obtained by drying the graphene dispersion liquid can be dispersed again in a solvent to form a film, and a film can be formed without aggregation of the graphene particles or the mixture of graphene and modified graphite. The method for drying the graphene dispersion to produce the graphene resin powder is not particularly limited, and examples thereof include a method for volatilizing the solvent in the graphene dispersion by vacuum heating at 60 to 120° C. to produce the graphene resin powder. The method for redissolving or dispersing the graphene resin powder in a solvent is not particularly limited, and examples thereof include a method in which the graphene resin powder is put into a solvent and stirred at a predetermined temperature (which may be room temperature) using mechanical stirring, ultrasonic waves, a high-pressure homogenizer, or the like. The solvent for redissolving the graphene resin powder is not particularly limited. Examples include polar solvents such as water, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, acetonitrile, tetrahydrofuran, dimethylsulfoxide, dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone. These may be used alone or in combination of two or more. Among these, water, methanol, ethanol, 1-propanol, 2-propanol, N-methylpyrrolidone, N,N-dimethylformamide, and a mixed solvent of at least two of these may be selected in terms of high affinity with graphene. The film-forming method using the dispersion liquid in which the graphene resin powder is redissolved is not particularly limited, and a method similar to the film-forming method using the graphene dispersion liquid can be used.
[0038] <Graphene dispersion for negative electrodes> The graphene resin powder of the present embodiment can be used as a graphene dispersion for a negative electrode by adding a negative electrode active material and a binder for a graphene dispersion for a negative electrode.
[0039] <<Negative electrode active material>> The negative electrode active material is not particularly limited as long as it can dope or intercalate lithium ions. Examples of the negative electrode active material include metallic Li; alloy-based materials such as tin alloys, silicon alloys, and lead alloys that are alloys thereof; Li k Fe2O3 (in this paragraph, k represents 0 < k ≤ 4), Li k Fe3O4, Li k Metal oxide-based materials such as WO2; Conductive polymer-based materials such as polyacetylene; Amorphous carbonaceous materials such as hard carbon; Artificial graphite such as highly graphitized carbon materials; Carbonaceous powders such as natural graphite; Carbon-based materials such as carbon black and carbon fiber. These negative electrode active materials can be used alone or in combination of two or more.
[0040] <<Binder for graphene dispersion for negative electrode>> The binder for graphene dispersion for negative electrode is not particularly limited as long as it is used to bind particles such as the active material and the conductive carbon material, or the conductive carbon material and the current collector. Examples of the binder for graphene dispersion for negative electrode include acrylic resin; polyurethane resin; Cellulose resins such as carboxymethyl cellulose; Synthetic rubbers such as styrene-butadiene rubber and fluororubber; Conductive resins such as polyacetylene; Polymer compounds containing fluorine atoms such as polyvinylidene fluoride. Further, the binder for graphene dispersion for negative electrode may be a modified product, a mixture, or a copolymer of these resins. These binders can be used alone or in combination of two or more. Further, when used in an aqueous sizing ink, a water-based binder can be used. Examples of the form of the water-based binder include a water-soluble type, an emulsion type, and a hydrosol type, and can be appropriately selected.
[0041] The graphene dispersion for negative electrode can further be blended with a film-forming aid, an antifoaming agent, a leveling agent, a preservative, a pH adjuster, a viscosity adjuster, etc. as required.
[0042] The graphene dispersion for a negative electrode can be used for an electrode for a lithium ion secondary battery, an electrode for an electric double layer capacitor, a primer layer for an electrode for a lithium ion capacitor, or the like.
[0043] <<Battery negative electrode mixture layer>> A battery negative electrode mixture layer can be obtained by coating and drying the graphene dispersion for a negative electrode on a current collector.
[0044] -Current collector- The material and shape of the current collector used in the electrode are not particularly limited, and can be appropriately selected from those suitable for various batteries. Examples of the material of the current collector include metals such as aluminum, copper, nickel, titanium, and stainless steel; and alloys of at least two of these. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, and a mesh-shaped current collector can also be used.
[0045] The method for applying the graphene dispersion for an electrode onto the current collector is not particularly limited, and a known method can be used. Examples of such methods include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting. Examples of drying methods that can be used include, but are not limited to, standing drying, blowing drying, hot air drying, infrared heating drying, and far-infrared heating drying. In addition, the current collector may be rolled using a lithographic press or a calendar roll after application.
[0046] (battery) The battery of this embodiment is, for example, a lithium ion secondary battery using a negative electrode that is a battery negative electrode mixture layer, a positive electrode, an electrolyte, a separator, and the like. The following description will be given taking a lithium ion secondary battery as an example.
[0047] <Electrolyte> The electrolyte solution may be a solution in which an electrolyte containing lithium is dissolved in a non-aqueous solvent. The non-aqueous solvent is not particularly limited, and examples thereof include carbonates such as ethylene carbonate and propylene carbonate; lactones such as γ-butyrolactone and γ-valerolactone; cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran; esters such as methyl formate and methyl acetate. These solvents may be used alone or in combination of two or more. Furthermore, the electrolyte solution may be held in a polymer matrix to form a gel-like polymer electrolyte. Examples of the polymer matrix include, but are not limited to, acrylate resins having polyalkylene oxide segments, polyphosphazene resins having polyalkylene oxide segments, and polysiloxanes having polyalkylene oxide segments.
[0048] Electrolytes include, but are not limited to, LiBF4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, and the like.
[0049] <Separator> Examples of the separator include, but are not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and those which have been subjected to a hydrophilic treatment. EXAMPLES
[0050] Next, the present disclosure will be specifically described with reference to examples, but the present disclosure is not limited to these examples in any way.
[0051] Example 1 [Method for preparing graphene dispersion] 20.00 g of modified graphite-1 (manufactured by XG sciences, grade M, size (long side): 15 μm, number of layers: 20 layers) was added to 575.00 g of a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) as a solvent, and treated with an ultrasonic homogenizer (manufactured by SMT Co., Ltd., UH-600S) for 60 minutes, and graphene was obtained from the modified graphite. Then, 28.80 g of carboxymethylated starch (manufactured by Nippon Starch Chemical Co., Ltd., product name: carboxymethyl starch, weight average molecular weight: 180,000, degree of etherification 0.90 to 1.10) as a polymer was added, and the mixture was mixed in a vacuum for 20 minutes using a planetary mixer to prepare a graphene dispersion. The prepared graphene dispersion is called dispersion 1. The following evaluations were carried out using the obtained Dispersion 1. The evaluation results are shown in Table 1-1.
[0052] [Graphene dispersion evaluation method] <Graphene concentration measurement, modified graphite concentration measurement, polymer concentration measurement> 20.00 g of modified graphite-1 (manufactured by XG sciences, grade M, size (long side): 15 μm, number of layers: 20 layers) was added to 575.00 g of a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) as a solvent, and 100.00 g of the mixture was treated for 60 minutes with an ultrasonic homogenizer (manufactured by SMT Co., Ltd., UH-600S). When the mixture was centrifuged with a centrifuge (manufactured by Hitachi Koki Co., Ltd., model: R-22N, 1000 rpm, 10 minutes), the supernatant was 90.00 g and the settled residue was 10.00 g. After drying 90.00 g of the supernatant at 100 ° C., the solvent was evaporated, and the solid content was 0.62 g. Therefore, 0.62 g of graphene and 89.38 g of solvent were contained in 90.00 g of the supernatant. The graphene concentration (mg / g) was calculated by dividing the graphene mass (0.62 g) by the solvent mass (89.38 g). The amount of graphene (g) in Tables 1-1 and 1-2 is a value obtained by multiplying the calculated graphene concentration (mg / g) by the amount of the solvent (g). In addition, the modified graphite concentration (mg / g) and polymer concentration (mg / g) in Tables 1-1 and 1-2 are respectively the value obtained by dividing the charged amount (mg) of modified graphite by the blended amount (g) of solvent and the value obtained by dividing the blended amount (mg) of carboxymethylated starch as a polymer by the blended amount (g) of solvent.
[0053] <Graphene size measurement> The graphene size (long side) was confirmed to be 0.70 μm using an atomic force microscope (Keysight Technologies, Model: AFM / SPM7500). The AFM sample was prepared by spray coating a graphene dispersion onto cleaved mica and drying.
[0054] <Graphene layer number measurement> The thickness of the graphene was measured using an atomic force microscope (Keysight Technologies, model: AFM / SPM7500). As a result, it was confirmed that the number of graphene layers was 10 or less, and that Modified Graphite-1 was graphene. The AFM sample was prepared by spray coating a graphene dispersion onto cleaved mica and drying.
[0055] <Graphene dispersion viscosity measurement> Using a Brookfield viscometer (manufactured by Horiba, Ltd., main body: LVT, cylindrical spindle: LV No. 4), the viscosity at 5 rpm and the viscosity at 50 rpm were measured at a measurement temperature of 25°C.
[0056] <Measurement of dispersibility of graphene dispersion> <<Dispersibility-1>> Dispersion 1 was left to stand at room temperature (25° C.) for one month, and precipitation and aggregation of graphene was visually observed and evaluated. A: No precipitation or aggregation occurs. B: A small amount of precipitation or aggregation occurs. C: A large amount of precipitation or aggregation occurs <<Dispersibility-2>> Dispersion 1 was centrifuged for 10 minutes using a centrifuge (Hitachi Koki Co., Ltd., model: CN-2060, rotor: RA-1508, 1000 rpm), and 1 mL of the dispersion was collected from the upper layer and diluted 100 times with a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) to prepare a diluted solution. The absorbance (660 nm) of the diluted solution was measured using a spectrophotometer (JASCO Corporation, V-570), and the absorbance value was calculated by multiplying the absorbance by 100.
[0057] [Evaluation of dispersibility and film-forming properties of graphene resin film] Dispersion Liquid 1 was dropped onto a metal foil, coated with a bar coater, and dried at 85° C. for 10 minutes to remove the solvent, forming a film with a thickness of 5 μm. The dispersibility and film-forming property of the formed graphene resin film were evaluated visually. <<Dispersibility>> A: No aggregation. B: Some aggregation is observed. C: Coagulation is present throughout. <<Film forming properties>> A: A uniform continuous film can be obtained. B: There are some areas where a uniform continuous film does not form. C: No film can be formed.
[0058] <Evaluation of electrical conductivity> The surface resistance of the graphene resin film having a thickness of 30 μm formed by the above method was measured using a Loresta (manufactured by Mitsubishi Chemical Analytical Co., Ltd.). The surface resistance value may be 1.0 Ω / □ or less, and may be 1.0×10 -1 It may be Ω / □ or less.
[0059] [Evaluation of dispersibility of graphene resin powder] The solvent of the dispersion liquid 1 was heated to 100° C. and dried, and the dried powder was then pulverized in a mortar to prepare graphene resin powder coated with a polymer. Using a dispersing rotor (three-one motor manufactured by Shinto Scientific Co., Ltd.) with a force weaker than that of ultrasonic waves, graphene resin powder was dissolved in 575 g of a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) as a solvent at 500 rpm for 10 minutes to prepare a graphene redispersion. The graphene redispersion was treated with a centrifuge (manufactured by Hitachi Koki Co., Ltd., model: CN-2060, rotor: RA-1508, 1000 rpm) for 10 minutes, 1 mL of the dispersion was collected from the upper layer, and diluted 100 times with a solvent to prepare a diluted solution. The absorbance (660 nm) of the prepared diluted solution was measured and multiplied by 100 to obtain the absorbance value.
[0060] (Examples 2 to 8, Comparative Examples 1 to 5) Graphene dispersions (dispersions 2 to 13) were prepared by blending the compositions shown in Tables 1-1 and 1-2 in the same manner as in Example 1. Furthermore, the prepared graphene dispersions (dispersions 2 to 13) were used to carry out the same evaluations as in Example 1. The evaluation results are shown in Tables 1-1 and 1-2. Specifically, dispersion 9 containing no polymer was used as Comparative Example 1, dispersion 10 containing a predetermined amount of surfactant instead of a polymer was used as Comparative Example 2, dispersions 11 and 12 having viscosity ratios not corresponding to those of the Examples were used as Comparative Examples 3 and 4, and dispersion 13 containing a nanofiller exhibiting electrical conductivity similar to that of graphene instead of modified graphite was used as Comparative Example 5.
[0061] [Table 1-1]
[0062] [Table 1-2]
[0063] The details of the blended components shown in Tables 1-1 and 1-2 are as follows. Modified graphite-2 (XG sciences, grade M, size (long side): 25 μm, number of layers: 20 layers) Nanofiller (Alumina nanofiller, manufactured by Sumitomo Chemical Co., Ltd., product name: AA-03, size 0.4 μm) Carboxymethylated starch (manufactured by Nippon Starch Chemical Co., Ltd., product name: Carboxymethyl starch, weight average molecular weight: 340,000, degree of etherification: 0.90-1.10) Carboxymethyl cellulose (manufactured by Nippon Paper Industries Co., Ltd., product name: MAC350HC, weight average molecular weight: 340,000, degree of etherification: 0.78-0.88) Hydroxyethyl cellulose (Sumitomo Seika Chemicals Co., Ltd., product name: HEC-CF-H, weight average molecular weight: 700,000, degree of etherification: 0.90-1.20) Polyvinyl alcohol-1 (manufactured by Mitsubishi Chemical Corporation, product name: EG-05C, weight average molecular weight: 120,000, saponification degree: 87 mol%) Polyvinyl alcohol-2 (manufactured by Kuraray Co., Ltd., product name: PVA-217, weight average molecular weight: 1700) Polyacrylic acid (manufactured by Nippon Shokubai Co., Ltd., product name: DL-100, weight average molecular weight: 3500) Surfactant (Kao Corporation, product name: Neopelex G-65, molecular weight: 350)
[0064] In this way, graphene and a polymer having a weight-average molecular weight of 10,000 to 800,000 were dispersed in a solvent, and the viscosity measured at 25° C. and 50 rpm using a Brookfield viscometer was adjusted to 500 to 10,000 (mPa s). The viscosity measured at 25° C. and 5 rpm using a Brookfield viscometer was divided by the viscosity measured at 25° C. and 50 rpm using a Brookfield viscometer to obtain a viscosity ratio of 1.2 to 5.0 (to make the dispersion thixotropic (to make a dispersion having structural viscosity)). This was evident from a comparison between Examples 1 to 8 and Comparative Examples 1 to 5.
[0065] <Preparation of graphene dispersion for negative electrode> 10.00 g of the graphene resin powder produced from dispersion 1, 85.00 g of spherical graphite as a negative electrode active material, 5.00 g of a binder for a negative electrode, and 122.00 g of a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) were added, put into a planetary mixer and kneaded under vacuum, and further mixed with a 48% aqueous dispersion of styrene butadiene emulsion as a binder for the graphene dispersion for a negative electrode to obtain a graphene dispersion for a negative electrode with a solid content concentration of 45%. Dispersions 2 to 13 were also prepared by the same method.
[0066] <Preparation of Battery Negative Electrode Mixture Layer> A battery electrode mixture layer was produced using the graphene dispersion for the negative electrode and copper foil (thickness 18 μm) as a current collector. The graphene dispersion for the negative electrode was applied to a predetermined thickness using a doctor blade. This was vacuum dried at 120°C for 1 hour and punched out to 18 mmΦ. Furthermore, the punched battery negative electrode mixture layer was sandwiched between ultra-hard steel press plates, and the pressing pressure was 1,000 to 3,000 kg / cm against the battery negative electrode mixture layer. 2 Press so that the coating weight is 7-9mg / cm 2 , thickness 40-60μm, electrode density 1.6g / cm 3 Thereafter, the resultant was dried in a vacuum dryer at 120° C. for 12 hours to obtain a negative electrode for evaluation.
[0067] <Production of positive electrodes> In a planetary mixer, 90.00 g of lithium nickel oxide as a positive electrode active material, 5.00 g of acetylene black (HS-100 manufactured by Denka Co., Ltd.) as a conductive assistant, 5.00 g of KF polymer W7300 (PVDF) as a positive electrode binder, and NMP were added and mixed to prepare a positive electrode mixture slurry with a solid content concentration of 67%. The positive electrode mixture slurry was applied to aluminum foil (thickness 10 μm) to a predetermined thickness using a doctor blade. This was vacuum dried at 120°C for 1 hour and punched out to 18 mmΦ. Furthermore, the punched electrode was sandwiched between ultra-hard steel press plates, and a pressing pressure of 1,000 to 3,000 kg / cm was applied to the electrode. 2 The electrode was then dried in a vacuum dryer at 120°C for 12 hours to obtain a positive electrode for evaluation. The thickness was about 80 μm and the electrode density was about 3.5 g / cm.3 It was.
[0068] <High-rate discharge capacity retention> A constant current / constant voltage charge / discharge test was carried out using the lithium ion battery test cell prepared above. Charges from rest potential to 4.3V at 3.6mA / cm 2 The battery was charged at a constant current of 3.6 mA / cm. The battery was then charged at a constant voltage of 4.3 V, and the charging was stopped when the current value dropped to 15.0 μA. The battery was discharged at various current densities (3.6 mA / cm 2 (equivalent to 0.1C), and 72.0mA / cm 2 Each battery was discharged at a constant current of 1000 V (equivalent to 2.0 C) and cut off at a voltage of 2.8 V. The ratio of the discharge capacity at 2.0 C to the discharge capacity at 0.1 C was evaluated as the high-rate discharge capacity retention rate. Evaluation was based on the following criteria. The results of evaluation based on the following criteria are shown in Tables 1-1 and 1-2. A (Excellent): High-rate discharge capacity retention is 95% or more, within the acceptable range. B (Good): High-rate discharge capacity retention is 90% or more but less than 95%, within the acceptable range. C (slightly poor): High-rate discharge capacity retention is 80% or more but less than 90%, within the allowable range. D (Poor): High-rate discharge capacity retention rate is less than 80%, unacceptable.
[0069] <Binder> Styrene butadiene emulsion (SBR) as a binder for graphene dispersion for negative electrodes (JSR Corporation, product name: TRD2001, 48% solids aqueous dispersion) Polyvinylidene fluoride (PVDF) as a binder for the positive electrode (Kureha Corporation, product name: KF Polymer W7300, weight average molecular weight approximately 1,000,000) <Electrode active material> Positive electrode active material: Lithium nickel oxide (manufactured by JFE Mineral Co., Ltd., product name: 503LP, average particle size 11 μm) Negative electrode active material: spherical graphite (Nippon Graphite Industry Co., Ltd., product name: CGB-20, average particle size 20 μm)
[0070] From Tables 1-1 and 1-2, it was found that the batteries of Examples 1 to 8 exhibited better results in terms of high-rate discharge capacity retention than the batteries of Comparative Examples 1 to 5. In particular, when the graphene resin powder has high dispersibility (absorbance) and the graphene resin film has good film-formability, it is possible to obtain an electrode layer of a secondary battery excellent in high-rate discharge capacity retention.
Claims
1. A graphene dispersion in which graphene and a polymer are dispersed in a solvent, The size (long side) of the graphene is 0.5-2 μm, the polymer is an aqueous polymer or an anionic polymer, and is any one of carboxymethylated starch, carboxymethyl cellulose, hydroxyethyl cellulose, and polyvinyl alcohol having a saponification degree of 87 mol%, each having an etherification degree of 0.5 to 2.2; The weight average molecular weight of the polymer is 10,000 to 800,000; the solvent is a mixed solvent containing water and an alcohol, The polymer is contained in the solvent in an amount of 1 to 100 mg / g. The graphene dispersion has a viscosity of 500 to 10,000 (mPa s) measured using a B-type viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm, a value obtained by dividing the viscosity of the graphene dispersion measured using a Brookfield viscometer at a measurement temperature of 25° C. and a rotation speed of 5 rpm by the viscosity of the graphene dispersion measured using a Brookfield viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm is 1.2 to 5.0; Graphene dispersion.
2. Graphene resin powder obtained by drying the graphene dispersion according to claim 1.
3. A battery using the graphene resin powder according to claim 2.
Citation Information
Patent Citations
Method for preparing three-dimensional porous nano composite material of graphene oxide-water soluble polymer
CN103881278A
Method for preparing multi-layer graphene
CN105084346A
Preparation method of hyaluronic acid / graphene oxide / polyacrylamide composite hydrogel
CN106478962A
Mixed liquid, resin composite material, and method for producing resin composite material
JP2012224810A
Polyvinyl alcohol-based composite fiber and method for producing the same
JP2013155461A
